Prevalence and risk factors of elevated alanine aminotransferase among Korean adolescents: 2001-2014 - Ju Whi Kim; Kyung Jae Lee; Hye Ran Yang; Ju Young Chang; Jin Soo Moon; Young-Ho Khang; Jae Sung Ko (BMC, 2018)
Abstract Background An elevated alanine aminotransferase (ALT) level is a surrogate marker of non-alcoholic fatty liver disease (NAFLD), the most common liver disorder in adolescents. The majority of previous NAFLD studies in adolescents were performed in selected obese populations or had a cross-sectional design without a time-trend analysis. The purpose of this study was to estimate the prevalence and time trends of elevated ALT levels in a general adolescent population and to identify factors associated with ALT elevation. Methods We analysed data of adolescent participants (aged 10-18 years) from the Korean National Health and Nutrition Examination Survey 2001-2014, a representative sample of the general population in South Korea. Suspected NAFLD was defined as ALT elevation (> 30 U/L) without hepatitis B surface antigen. In all statistical analyses, sampling weight- and design-based data were used. Results ALT was elevated in 5.3% (standard error: 0.3%) of the study population of adolescent participants (N = 8455). No significant trends were found from 2001 to 2014 in the prevalence of elevated ALT among male and female adolescents. In multiple logistic regression analysis, elevated ALT was independently associated with sex (odds ratio [OR] male versus female 4.5; 95% CI, 3.3-6.2), obesity (OR 7.6; 95% CI, 5.3-11.0), and truncal obesity (OR 2.5; 95% CI, 1.8-3.5). Furthermore, male sex, obesity, truncal obesity and high household income level were associated with log-transformed ALT levels in multiple regression analysis. Conclusions In Korean adolescents of both genders, the prevalence of elevated ALT levels was stable from 2001 to 2014. This study has revealed that sex, obesity, truncal obesity and household income level are associated with ALT elevation in adolescents.